2012
DOI: 10.1242/jeb.076893
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic expression of transcortin in neural cells of the mouse brain: a histochemical and molecular study

Abstract: SUMMARYCorticosteroid binding globulin (CBG, transcortin) has been shown to be expressed in the brain of rat and human species. In this study, we examined the CBG brain expression and cDNA structure in mice, comparing wild-type (Cbg

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…Although hypothetical, the local expression of CBGs in brain may account for this discrepancy. CBGs are widely expressed in rodent and human brain, 25,54‐56 and, although their function is still unclear, they may serve as cellular mediators of CORT action in the absence of CORT receptors or as mechanisms enhancing CORT transport to classical receptors 26,57 . The songbird CBG sequence has recently been identified 58 and our very preliminary work suggests that the protein is expressed, albeit at quite low levels, in the zebra finch brain (M.A.…”
Section: Discussionmentioning
confidence: 85%
“…Although hypothetical, the local expression of CBGs in brain may account for this discrepancy. CBGs are widely expressed in rodent and human brain, 25,54‐56 and, although their function is still unclear, they may serve as cellular mediators of CORT action in the absence of CORT receptors or as mechanisms enhancing CORT transport to classical receptors 26,57 . The songbird CBG sequence has recently been identified 58 and our very preliminary work suggests that the protein is expressed, albeit at quite low levels, in the zebra finch brain (M.A.…”
Section: Discussionmentioning
confidence: 85%
“…GCs can also be preferentially imported into (or out of) cells and tissues by ATP-binding cassette (ABC) transporters, potentially resulting in local accumulation of specific GCs that are present in circulating blood (12,44). Finally, GCs may be sequestered by high-affinity binding to membrane and cytoplasmic proteins, such as corticosteroid-binding globulin (39) and glutathione S-transferase (40,41). Such proteins could affect access of GCs to their cognate receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of both CBG mRNA and protein have been identified that are localized to the hippocampus (Sivukhina et al, 2013a, 2013b, 2006), and it appears that CBG expression in hippocampal tissue is intrinsic rather than derived from cerebrospinal fluid or plasma (Jirikowski et al, 2007; Orchinik et al, 1997; Sivukhina and Jirikowski, 2014). Thus, it is possible that decreased extracellular CBG could prolong stress-induced elevations in free extracellular corticosterone levels in the ventral hippocampus that are not observed in the plasma.…”
Section: Discussionmentioning
confidence: 99%